ANALISIS KANDUNGAN KIMIA BUAH TERONG BELANDA (Cyphomandra betacea) SETELAH DIOLAH MENJADI MINUMAN RINGAN - Anna Suzanna; Mohammad Wijaya; Ratnawaty Fadilah (Jurnal Pendidikan Teknologi Pertanian, 2022)
The purpose of this study was to determine changes in the chemical content of the Dutch eggplant (C. betacea) after being processed into soft drinks. The experimental design used was a Completely Randomized Design (CRD) consisting of the concentration of addition of granulated sugar, namely: 0% (Control), 10%, 20% and 30%. The parameters observed in this study were chemical analysis (total sugar, fiber, vitamin C, anthocyanin, pH value) and organoleptic value of soft drinks. The results showed that sugar use affected changes in total sugar, fiber, vitamin C, anthocyanin and the pH value of soft drinks. Likewise the likes or acceptance of the panelists. The best treatment in terms of chemical and organoleptic tests, soft drinks with additional sugar content of 20% with total sugar 5.12%, crude fiber 0.16%, vitamin C 0.0223%, anthocyanin 47.52% and pH 5.67% , aroma value 7.3, taste value 7.5 and color value 5.05.